Transformasi Konsep Kegiatan Perpustakaan Berbasis Inklusi Sosila di Masa Pandemi (Studi Kasus Perpustakaan Universitas Teknokrat Indonesia) - Iqbal, Rahmat; Soleha, Nadya Amalia (UIN Raden Intan Lampung, 2022)
The University Library is an integrated library of educational, research and community service activities and functions as a learning resource center to support the achievement of educational goals located in higher education. The library provides various kinds of information that can help people who do not have a job base by providing information about the job market and providing training or practice for someone to be able to become an entrepreneur. The author uses qualitative research with library research methods. In collecting data, the author makes observations, documentation and direct interviews. From the recap in January-April, it shows that there has been an increase in student interest in visiting the library, this is shown by the number that continues to increase every month. From this it can be concluded that library activities have a very effective role in attracting student visits. Therefore, it is proper for us librarians to present activities that increase knowledge and knowledge in the university environment. The increase in interest in visiting is always accompanied by interest in borrowing/reading library users.